Inter-linkages among various components of dairy based farming systems in Mizoram State - Lalrinsangpuii, Lalrinsangpuii; R, Malhotra (The Indian Journal of Agricultural Sciences, 2020)
Farming system approach has been widely recognized and advocated as one of the tools for harmonious use of inputs and their compounded response to make the production system sustainable. The present study was conducted to examine linkages among various components of farming systems in Mizoram state by using Leontief input-output model. The study identified 10 dairy based farming systems based on the major contribution to income of farm enterprise. The inter-component linkages from livestock to crop were stronger as compared to crop to livestock for all the farming systems. The degree of integration of different components of the various farming systems in terms of linkages is found to be strongest under D + C + P + Po farming systems. The interdependence observed among various components of farming system suggests the need to adopt total systems approach for development of sustainable farming systems.